Factors influence the dividend policy in Malaysia / Nurul Hamizah Hamdan - Hamdan, Nurul Hamiza (Faculty of Business Management, 2017)
This study investigates the factors influencing dividend policy of companies in Malaysia. The issues of this study is to know of what reallyinfluence the dividend policy in Malaysia. Besides that, the purpose of this researchis to have a clear view on the what really influence the dividend policy and to study the interactionbetween the dependent variable of dividend policy and independent variables of investment opportunities, growth opportunities, leverage , firm size and earnings growth. The data observation data are collected for 215 observations of 43 companieslisted in Bursa Malaysia are collected through Osiris. The data has been analyzed by using Eviews 8.0 to do descriptive, correlation and regression analysis and test on assumption. The findings for the five year period from year 2011 to 2015 indicates earnings per share (EPS) , market-to-book value (MTBV) and price earning (PE) have a positive significant relationship with the dividend policy. While, debt-to-equity (DER) and total assets (TA) have negative insignificant relationship with dividend policy.